Legal Analysis of Restrictions on the Political Rights of Exconvicts to be Elected in Local Elections Regional Head Election - Wiridin, Darmawan; Mustafa, Ali; Nasrin; Aisyah, Sitti; Putra, Zulfikar (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The purposes of this study are: 1) To find out the restrictions on the political rights of ex-convicts to participate in the election of Regional Heads 2) To find out the legal consequences of restrictions and revocation of political rights of ex-convicts to be elected in regional head elections. The type of normative legal research is doctrinal legal research or library research. The results of the researchare: 1) Limiting the political rights of ex-convicts to be elected is contrary to the hierarchy higher regulations. Based on Law No.12 of 2011 concerning the Formation of Legislation and Invitation and is not in line with the principle (Lex Superior Derogat Legi Inferiori) meaning that the reshould be nolower regulations contrary to higher regulations. 2) Due to the law limiting the political rights of ex-convicts to be elected, it can be canceled through are quest for examination. Judicial review at the Supreme Court based on Law Number 12 of 2011 concerning the Establishment of Legislation, Law Number 39 of 1999 concerning Human Rights and Law Number 7 of 2017 concerning General Elections